The synergistic effect of inorganic hybrid nanofibers and phytic acid-based nanosheets towards improving the fire retardancy and comprehensive performance of epoxy resin - Suhua Zhang; Zhenzhong Wu; Shihu Han; Yiqing Wang; Lijun Qian; Xiaoping Hu (eXPRESS Polymer Letters, 2023)
Usually, it is difficult to achieve satisfactory fire retardancy of epoxy resin (EP) at low addition by adding inorganic nano-fillers alone. Herein, sepiolite nanofibers loaded with layered double metal hydroxide (a-SEP@LDH) and phosphorus/nitrogen-containing flame retardant nanosheets (PAMA) were prepared via hydrothermal method, respectively. The UL-94 V-0 rating and an limiting oxygen index (LOI) value of 31.6% were achieved for EP by loading 1 wt% a-SEP@LDH and 2 wt% PAMA. Compared to adding sole a-SEP@LDH, the thermal stability of EP/a-SEP@LDH/PAMA3 was improved significantly, the total heat release (THR) and peak heat release rate (pHRR) decreased by 10.2 and 28.8%, respectively. Additionally, the total CO2 production decreased by 12.5% and the char residue yield increased to 19.9 wt%. Moreover, the tensile strength and impact strength of the EP composites were remarkably improved owing to the incorporation of PAMA. To sum up, this work provides an environmentally benign, low-cost and efficient way for EP to achieve outstanding fire retardance, thermal stability and high mechanical properties at a low addition.